What makes playgroups therapeutic? A scoping review to identify the active ingredients of therapeutic and supported playgroups - Armstrong, J.; Paskal, K.; Elliott, Catherine; Wray, J.; Davidson, E.; Mizen, J.; Girdler, Sonya (Informa Healthcare, 2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Background: Supported and therapeutic playgroups aim to support and strengthen vulnerable children and families by increasing parenting capacity, parent-child interaction, enhancing child outcomes and promoting community networks. This review aimed to comprehensively scope the literature to identify the “active ingredients” of supported and therapeutic playgroups. Method: A systematic search of grey and scholarly literature was conducted using Medline, PyschINFO, EMBASE, ERIC, CINAHL, MedNar, Informit, Scopus, Libraries of Australia and Trove. Articles were included if they: i) defined playgroup as a group of children and actively involved caregivers; ii) described a therapeutic playgroup or supported playgroup model; iii) targeted children prior to school age; and iv) measured the impact of playgroups. A total of 36 articles met the inclusion criteria. Qualitative data was synthesised using a meta-ethnography approach with findings charted against a conceptual model of engagement. Quantitative data was synthesised using descriptive statistics. Results: The findings identified that emotional, practical and informational components of playgroups strongly reflect family centred practice, self-efficacy theory and peer-support principles. Conclusion: Therapeutic and supported playgroups are complex interventions, with numerous interacting components that make them beneficial for children and families. This review is the first to identify the “active ingredients” of playgroups with findings informing the design of future playgroups for vulnerable children and families.